Video Assistant Referee (VAR), gender and football refereeing: a scoping review - Skirbekk, S. (Soccer & Society, 2024)
The increasing use of VAR globally affects the refereeing role and may have unintended gendered consequences for referees. This scoping review 1) summarizes and maps the research on refereeing, gender, and VAR in football, 2) identifies and analyzes knowledge gaps in the field, and 3) suggests recommendations for practice, and future research. The review indicates that the combination of gender and technology, and how they impact the refereeing role, is not featured in research. Instead, VAR studies mainly focus on the outcome of decisions, while research on gender and refereeing concerns individual experiences of female referees. The review further shows the implementation of certain technologies in football, and their consequences for male and female referees, has not received the scholarly attention it deserves. Future studies should utilize organizational, intersectional, and medial perspectives to understand how VAR and other novel refereeing technologies can be used to achieve gender equity in refereeing.